Endourological treatment of upper tract urinary disease in children - Ha, Darren; Harris, Kelly T.; Rove, Kyle O. (Frontiers in Urology, 2023)
With advances in therapeutic interventions, endourology has become standard of care for the treatment of numerous diseases in the field of pediatric urology. However, there remains a lack of agreement and evidence on the optimal approaches and associated complications of endourological treatment of upper urinary tract conditions in children, namely ureteropelvic junction (UPJ) obstruction, primary obstructive megaureter, and nephrolithiasis. While pyeloplasty remains the first-line surgical treatment for pediatric UPJ obstruction, endoscopic retrograde balloon dilatation (ERBD) and endopyelotomy continue to gain traction as less invasive means of treating obstruction. Studies report success rates ranging from 76-100% although re-stenosis or need for revision surgery is not uncommon. Endourological options for the surgical management of primary obstructive megaureter include ERBD or endoureterotomy. Both have shown long-term success rates ranging from 70-90%, however, there is emerging evidence that these therapies may be associated with a risk of postoperative vesicoureteral reflux. Meanwhile, for stone disease, shock wave lithotripsy, ureteroscopy (URS), and percutaneous nephrolithotomy (PCNL) are mainstays in the pediatric urologist’s armamentarium. Studies have shown that URS and PCNL have comparable stone-free rates, although PCNL can be associated with increased morbidity. The rise of endourology expertise and improved technology makes it an attractive option that could even be considered as first-line for the treatment of various urinary tract conditions. This review aims to summarize results of endourological treatments for pediatric UPJ obstruction, primary obstructive megaureter, and nephrolithiasis, as well as highlight advancements in the field that may increase its utilization in pediatric urology in the future.